Phoenix from the ashes? Russia's defence industrial complex and its arms exports - Mitchell, Cameron Scott
The continued existence of the Russian defence and arms industry (OPK) was called into question following the disintegration of the Soviet Union in 1991. Industry experts cited the lack of a domestic market, endemic corruption, and excess capacity within the industry as factors underpinning its predicted demise. However, the industry's export customers in China, India and Iran during those early years became the OPK's saving grace. Their orders introduced hard currency back into the industry and went a long way to preventing the forecasted OPK collapse. Although pessimistic predictions continued to plague the OPK throughout the 1990s, the valuable export dollars provided the OPK the breathing space it needed to claw back its competitive advantage as an arms producer. That revival has been further underpinned by a new political commitment, various research and development initiatives, and the restoration of defence industry as a tool of Russian foreign policy. The short-term future of the Russian OPK looks promising. The rising domestic defence order is beginning to challenge the export market as the OPK's most important customer. Meanwhile, exports will be safeguarded by continued foreign demand for niche Russian defence products. Although the long-term future of the OPK is more difficult to predict, Russia's solid research and development foundation and successful international joint military ventures suggest that the current thriving trend in exports is likely to continue. Russia represents the next generation of affordable and rugged military equipment for the arsenals of the developing world. Coupled with Russia's growing ability to rearm itself through higher oil prices and a more streamlined defence industry, the future of the OPK looks bright
Keywords: Geschichte 1992-2008; Armes; Economic history; Economics; POLITICAL SCIENCE; Social conditions; Weapons industry; Weapons industry -- Russia; Rüstungsindustrie; Russland; Russia (Federation) / Economic aspects; Russia (Federation) / Economic conditions; Russia (Federation) / Social conditions; Russia (Federation); Russia; Electronic books